IoT-based Distribution and Control System for Smart Home Applications - Rokonuzzaman M.; Akash M.I.; Khatun Mishu M.; Tan W.-S.; Hannan M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automation; Domestic appliances; Electric power transmission networks; Energy management; Energy management systems; Humidity control; Intelligent buildings; Internet of things; Smart power grids; Distribution systems; Home energy management system; Home energy management systems; Home-application; Internet of thing; Power distributions; Smart control; Smart grid; Smart homes; Smart socket; Control systems